AUTOMATED METHODOLOGY FOR SCENARIO GENERATION AND ITS FEASIBILITY TESTING - Park, Sang C.; Ahn, Euikoog; Kwon, Yongjin (James) (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
The main purpose of this study is to devise a novel methodology for automated scenario generation, which simultaneously checks the feasibility and the correctness of scenarios in terms of event sequence, logical propagation, and violation of constraints. Modern day warfare is highly fluidic, fast moving, and unpredictable. Such situation stipulates the fast decision making and rapid deployment of fighting forces. Management of combat assets and utilization of battlefield information, therefore, become the key factors that deice the outcome of engagement. In this context, the Korean Armed Forces are building a framework, in which commanders can rapidly and efficiently evaluate every conceivable engagement scenario before committing real assets. The methodology is derived from the Conflict Table, event transition probabilities, DEVS formalism, and DFS algorithm. The presented example illustrates an one-on-one combat engagement scenario with two submarines, of which results validate the effectiveness of the proposed methodology.